Impact of Low Inclusion Rate of Olive Cake in Dairy Cow Rations on Uterine Health and Fertility Indices During Early Lactation - Ioannis Nanas; Themistoklis Giannoulis; Eleni Dovolou; Ilias Giannenas; Georgios S. Amiridis (Animals)
Olive cake was incorporated at a low inclusion rate (3.7%) into the rations of dairy cows through partial substitution of maize, and its effects on milk production, general health, and fertility traits were investigated. Multiparous purebred Holstein dairy cows (n = 148) were divided into two groups: a treated group (n = 86) and a control group (n = 62). The control ration (group C) was modified by replacing 1 kg of maize with an equal quantity of olive cake (group T). The experiment lasted from 60 days prepartum to 150 days postpartum. Electronic aids were utilized to quantify daily milk yield and detect estrus expression, while clinical and uterine examinations were performed weekly. Blood samples, uterine epithelial cells, and endometrial tissue samples were collected from a subgroup of healthy animals in both groups at specific time points. Blood samples were examined to determine the β-hydroxybutyric acid (BHBA), acute phase proteins (haptoglobin [Hpt] and serum amyloid A [SAA]), progesterone, and pregnancy-associated glycoproteins concentrations. Uterine epithelial cells were assessed for polymorphonuclear neutrophil (PMN) counts, and the expression of nine genes encoding inflammatory cytokines and immune system activation was analyzed in uterine biopsy tissue. No significant differences (p > 0.05) were observed between groups in milk yield, general morbidity, clinical endometritis, or conception rates. However, animals in group T came to estrus approximately 6 days earlier (p = 0.013) than those in group C; progesterone concentrations on day 7 of the subsequent cycle tended (p = 0.07) to be higher in group T. On day 21, BHBA concentrations were higher in group C than in group T (p < 0.05). Throughout the experiment, Hpt levels in group T were consistently lower (p < 0.001), while SAA was lower on day 7 compared to group C. From days 21 to 42 postpartum, there was a significant reduction in PMN numbers (group C p = 0.02; group T p < 0.0001), with a tendency for a greater reduction rate in group T (p = 0.08). Among the genes studied, a significant difference was revealed in the expression of the ILA1 gene, with strong correlations of gene expression in group C and weak to moderate correlations in group T. In conclusion, under the conditions of this experiment, the inclusion of olive cake into dairy cows’ rations did not affect milk production but improved certain health and fertility parameters, making olive cake a suitable alternative feedstuff for high-producing animals.